Molecular simulation of permeation behaviour of ethanol/water molecules with single-layer graphene oxide membranes. Issue 10 (3rd July 2018) - Yu, Tongfei; Bai, Lifei; Xu, Zhijun; Yang, Xiaoning
Abstract: Graphene oxide (GO)-based materials have shown promise as water-permeating membranes in pervaporation separation. However, the feed permeation and surface affinity of single-layer nanoporous GO sheet for liquid mixtures remain unresolved. Here, the pressure-driven molecular transport of pure ethanol and pure water, as well ethanol-water mixtures, crossing through single-layer nanoporous GO sheet was studied by non-equilibrium molecular dynamics simulations. We show that single-layer GO sheet with controlled pore sizes can effectively reject ethanol and allow water permeation with high permeability. This means that porous GO sheets could act as an effective dehydration membrane, therefore providing the initial barrier for ethanol passage in GO-based membrane. The pore size effect was considered as the separation mechanism. Both ethanol and water molecules in the mixture show comparable affinity with GO surfaces. The hydrogen-bonding coupling interaction between mixture and surface functional groups provide addition influence on the molecular transport through GO pores.